Savings and Investment Behaviour of Academicians After the Withdrawal of Income Tax Deductions - Singh, Khujan; Devi, Aarti; Jyoti (Indian Journal of Finance, 2022)
This paper attempted to assess the tax-saving investment behavior of the academicians of Hisar district of Haryana after the withdrawal of tax deductions by using primary data. The primary data were collected from 337 respondents through a self-structured questionnaire and analyzed with Cronbach’s alpha, analysis of variance, Welch test, and multiple mean comparisons test (post-hoc test). The study found an insignificant difference in savings and investment behavior of academicians with regard to their savings in banks/post office/and cooperative banks, five-year bank/post office fixed deposits, public provident fund, health insurance, life insurance, term life insurance, unit-linked insurance plan, national saving certificate, employees provident fund/general provident fund, mutual funds, real estate, gold exchange trade fund, stock market, recurring deposits, and systematic investment plan even after the withdrawal of tax deductions across the different income levels. The current study will be helpful for government authorities and policymakers to understand the investment behavior of individuals after the withdrawal of tax deductions.